Addressing social isolation and suicide risk in South Korea's permanent rental housing: An empirical investigation of intervention Strategies - Kiduk Park (Heliyon)
This study examines social isolation and suicide risk in South Korea's permanent rental housing, which has been in existence since 1989. The research objectives are threefold: firstly, to identify individuals and households at heightened risk of mental health challenges; secondly, to analyze the causal relationships between residential environments and mental health outcomes; and thirdly, to formulate evidence-based recommendations for suicide prevention interventions. The study employs data from the Housing Management Agency and the Korea Welfare Panel Survey (KOWEPS) to emamine a range of factors, including household composition, age, gender, housing satisfaction, and social relationships. The study's key findings indicate an elevated prevalence of suicide and loneliness, particularly among older adults and single-person households. Significant influences on these outcomes include financial stress, housing tenure, neighborhood characteristics, and housing quality. The study identifies depression as a critical factor, influenced by self-esteem, social support, and environmental satisfaction, with older residents with lower education and employment rates being most at risk. The research underscores the need for demographically targeted mental health strategies and highlights the importance of expanded public health interventions and housing improvements. It advocates for early identification and proactive management of mental health risks, emphasizing a comprehensive approach to reducing social isolation and suicide in permanent rental housing.